The role of track changes in enhancing editing accuracy: Disentangling tool effect and metacognitive learning processes in academic manuscript editing - Arsanti, Meilan; Zulaeha , Ida; Subyantoro, Subyantoro; Setyaningsih , Nas Haryati; Wardani, Oktarina Puspita (BAHASTRA, 2026)
While the digitization of academic editing is often considered to linearly improve performance, the internal mechanisms that differentiate the impact of tools and learning processes are rarely explored. This study aims to analyze the effects of using the Track Changes feature on editing accuracy and its relationship to metacognitive regulation and cognitive load of aspiring editors. Using a quasi-experimental Non-equivalent Control Group Design, this study involved aspiring student editors divided into an experimental group (Track Changes) and a control group (conventional). Data were collected through an editing accuracy test and analyzed using Normalized Gain and Cohen's d effect size. The results showed that the experimental group experienced a significant increase in editing accuracy (g = 0.53) compared to the control group (g = 0.19). Inferential analysis yielded a Cohen's d value of 1.18, indicating a large effect of tool use on editorial performance. These findings demonstrate that Track Changes functions as a cognitive scaffold that reduces external cognitive load, particularly on surface-level errors such as mechanics and typography. However, improvements in logic and discourse were limited, suggesting that this technology is more effective as a metacognitive mediator than as a substitute for higher-order linguistic reasoning. The unique contribution of this study lies in the empirical separation of the tool's technical impact from natural learning progression, which provides a theoretical basis for integrating technology into professional editing education curricula.